A cross-country comparison of intensive care physicians’ beliefs about their transfusion behaviour: A qualitative study using the theoretical domains framework - Islam, Rafat; Tinmouth, Alan T; Francis, Jill J; Brehaut, Jamie C; Born, Jennifer; Stockton, Charlotte; Stanworth, Simon J; Eccles, Martin P; Cuthbertson, Brian H; Hyde, Chris; Grimshaw, Jeremy M (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background Evidence of variations in red blood cell transfusion practices have been reported in a wide range of clinical settings. Parallel studies in Canada and the United Kingdom were designed to explore transfusion behaviour in intensive care physicians. The aim of this paper is three-fold: first, to explore beliefs that influence Canadian intensive care physicians’ transfusion behaviour; second, to systematically select relevant theories and models using the Theoretical Domains Framework (TDF) to inform a future predictive study; and third, to compare its results with the UK study. Methods Ten intensive care unit (ICU) physicians throughout Canada were interviewed. Physicians’ responses were coded into theoretical domains, and specific beliefs were generated for each response. Theoretical domains relevant to behaviour change were identified, and specific constructs from the relevant domains were used to select psychological theories. The results from Canada and the United Kingdom were compared. Results Seven theoretical domains populated by 31 specific beliefs were identified as relevant to the target behaviour. The domains Beliefs about capabilities (confident to not transfuse if patients’ clinical condition is stable), Beliefs about consequences (positive beliefs of reducing infection and saving resources and negative beliefs about risking patients’ clinical outcome and potentially more work), Social influences (transfusion decision is influenced by team members and patients’ relatives), and Behavioural regulation (wide range of approaches to encourage restrictive transfusion) that were identified in the UK study were also relevant in the Canadian context. Three additional domains, Knowledge (it requires more evidence to support restrictive transfusion), Social/professional role and identity (conflicting beliefs about not adhering to guidelines, referring to evidence, believing restrictive transfusion as professional standard, and believing that guideline is important for other professionals), and Motivation and goals (opposing beliefs about the importance of restrictive transfusion and compatibility with other goals), were also identified in this study. Similar to the UK study, the Theory of Planned Behaviour, Social Cognitive Theory, Operant Learning Theory, Action Planning, and Knowledge-Attitude-Behaviour model were identified as potentially relevant theories and models for further study. Personal project analysis was added to the Canadian study to explore the Motivation and goals domain in further detail. Conclusions A wide range of beliefs was identified by the Canadian ICU physicians as likely to influence their transfusion behaviour. We were able to demonstrate similar though not identical results in a cross-country comparison. Designing targeted behaviour-change interventions based on unique beliefs identified by physicians from two countries are more likely to encourage restrictive transfusion in ICU physicians in respective countries. This needs to be tested in future prospective clinical trials.